2023
DOI: 10.1097/mog.0000000000000920
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic dysfunction and nonalcoholic fatty liver disease risk in individuals with a normal body mass index

Abstract: Purpose of review Nonalcoholic fatty liver disease (NAFLD) is strongly associated with obesity, but is also common in individuals with a normal body mass index (BMI), who also experience the hepatic inflammation, fibrosis, and decompensated cirrhosis associated with NAFLD progression. The clinical evaluation and treatment of NAFLD in this patient population are challenging for the gastroenterologist. A better understanding of the epidemiology, natural history, and outcomes of NAFLD in individuals w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 55 publications
(79 reference statements)
0
1
0
Order By: Relevance
“…Nonetheless, in recent years, chronic non-communicable diseases have become the leading cause of death in prisons, mainly driven by cardiovascular and metabolic-related events, which are significantly more frequent in patients with concomitant advanced liver disease due to MASLD [35]. Our results confirmed the impact of metabolic disorders in the penitentiary population [36], putting the spotlight on the need for screening programs and targeted therapeutic interventions and reinforcing the role of abdominal circumference instead of body mass index as a marker of adiposity [37].…”
Section: Discussionsupporting
confidence: 73%
“…Nonetheless, in recent years, chronic non-communicable diseases have become the leading cause of death in prisons, mainly driven by cardiovascular and metabolic-related events, which are significantly more frequent in patients with concomitant advanced liver disease due to MASLD [35]. Our results confirmed the impact of metabolic disorders in the penitentiary population [36], putting the spotlight on the need for screening programs and targeted therapeutic interventions and reinforcing the role of abdominal circumference instead of body mass index as a marker of adiposity [37].…”
Section: Discussionsupporting
confidence: 73%
“…Moreover, considering that lean individuals often have normal body size, but may have abnormalities in visceral fat, BMI cannot be used as the sole indicator to assess the severity and prognosis of NAFLD. One review article suggested visceral adiposity may be a critical risk factor for lean-NAFLD [ 15 ]. Furthermore, previous studies have shown that compared to BMI and WC, waist-hip ratio (WHR) is a superior predictor of visceral fat, which is strongly linked to fatty liver [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%